Tourism Education in the Tourism Industry as a Key to Competitiveness - Romanova, Galina; Romanov, Sergei; Popov, Alexey; Kushevsckaya, Raisa (International Review of Management and Marketing, 2016)
Over recent decades, tourism development in most countries has become an ultimately favoured and viable area of business and commerce. Travel and tourism industry is seen both as a highly profitable option for investment, and a solid source of new jobs and national income. These advantages of tourism are considerably stronger than benefits of other economic activities. Tourism is also an agent in good-neighbourly relations of peoples and nations, which is a very important role in the modern context. The article shares outcomes of a SWOT analysis of the current system of tourism higher education in Russia by presenting a structured assessment of the situation, findings of the survey regarding tourism employer’s satisfaction with the graduates’ higher education quality in the Services and Tourism fields. Results of the criteria-based quality assessment of the graduates’ higher education quality, and the list of most significant criteria for benchmarking graduates’ higher education quality and employers’ needs. Keywords: education quality assessment, tourism, hotel business JEL Classifications: L83, Z32